Letter to the Editor on Risk Factors, Outcomes, and Timing of Manipulation Under Anesthesia After Total Knee Arthroplasty (2018)
We read with great interest the study by Newman et al regarding risk factors and different timing of manipulation under anesthesia (MUA) in patients with stiffness after total knee arthroplasty (TKA) [1]. We would like to congratulate authors for such an interesting publication considering the appropriate design to answer the questions; however, there are some comments we would like to add in order to contribute to a better understanding of its clinical application.